2011
DOI: 10.1038/ng.788
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies somatic mutations of DNA methyltransferase gene DNMT3A in acute monocytic leukemia

Abstract: Abnormal epigenetic regulation has been implicated in oncogenesis. We report here the identification of somatic mutations by exome sequencing in acute monocytic leukemia, the M5 subtype of acute myeloid leukemia (AML-M5). We discovered mutations in DNMT3A (encoding DNA methyltransferase 3A) in 23 of 112 (20.5%) cases. The DNMT3A mutants showed reduced enzymatic activity or aberrant affinity to histone H3 in vitro. Notably, there were alterations of DNA methylation patterns and/or gene expression profiles (such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
658
7
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 733 publications
(707 citation statements)
references
References 46 publications
38
658
7
4
Order By: Relevance
“…We and others 24,25,29 --31,44 found that DNMT3A mutations were strongly associated with FAB M4/M5 subtypes, and often co-occurred with NPM1 or IDH1 mutations in AML patients, suggesting that the oncogenic actions of these mutations are not redundant. DNMT3A mutations were reported to be associated with older age, 24,25,30,31 but this feature was not observed in our cohort of adult CN-AML. Nevertheless, a link between age and the incidence of DNMT3A mutations is likely as these mutations seem to be extremely rare (o1%) in pediatric AML.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…We and others 24,25,29 --31,44 found that DNMT3A mutations were strongly associated with FAB M4/M5 subtypes, and often co-occurred with NPM1 or IDH1 mutations in AML patients, suggesting that the oncogenic actions of these mutations are not redundant. DNMT3A mutations were reported to be associated with older age, 24,25,30,31 but this feature was not observed in our cohort of adult CN-AML. Nevertheless, a link between age and the incidence of DNMT3A mutations is likely as these mutations seem to be extremely rare (o1%) in pediatric AML.…”
Section: Discussioncontrasting
confidence: 77%
“…45 --47 Among the 11 different DNMT3A mutations identified in our cohort, those affecting R882 residue were the most common, in agreement with previous reports. 24,25,29 Interestingly, the somatic R882 mutations in DNMT3A found in AML are analogous to the inherited R823G mutation in DNMT3B, which was discovered in a human syndrome characterized by immunodeficiency, centrosome instability and facial abnormalities (ICF) in association with defects in genomic methylation. 48,49 In AML, the exact pathogenic mechanism by which DNMT3A mutations act is still enigmatic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations